Analisis Visual Nilai Moral Kepahlawanan Dalam Film Jendral Soedirman Karya Tubagus Deddy - Dewi, Ni Putu Sinta (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The choice of Jendral Soedirman's film is because visually there is an exemplary content related to the moral values ​​played by the main character General Soedirman in the film. The formulation of the problem in this writing is about how the visual analysis of moral values ​​in the film General Soedirman? The purpose of this paper is visually to find moral values ​​that can be used as a reference in living a religious social life. The research method in writing this paper uses descriptive qualitative research methods. The research approach used in this paper is Pirce's semiotics which divides signs into three parts, namely icons, indexes and symbols. This paper will discuss the results of visual analysis regarding the moral values ​​contained in the film Jenderal Soedirman. Based on a visual analysis of the film Jendral Soedirman, several moral values ​​were found, namely those related to responsibility, conscience, and social moral values. The film, entitled Jendral Soedirman, is based on the true story of the struggle of a warlord in quelling the cruelty and injustice committed by the Dutch against the Indonesian people. In this scene, the film highlights the figure of General Soedirman who fights for and defends the Indonesian state, showing how hard General Soedirman's struggle is in defending the Indonesian state in the midst of his condition, which is suffering from illness and having to leave his family. The film entitled Jendral Soedirman has a social, informative, educative and persuasive function in providing an understanding of moral values ​​that should be emulated, especially by the nation's next generation in the digital and rapidly developing era of technology. Visually learning about moral values ​​is comprehensively explored in the film General Soedirman.